2020
DOI: 10.1039/d0ew00045k
|View full text |Cite
|
Sign up to set email alerts
|

Landfill leachate contributes per-/poly-fluoroalkyl substances (PFAS) and pharmaceuticals to municipal wastewater

Abstract: Widespread disposal of landfill leachate to municipal sewer in the US calls for improved understanding of the relative organic-chemical contributions to the WWTP waste stream and associated surface-water discharge to receptors in the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 61 publications
7
52
0
3
Order By: Relevance
“…Similar findings have been reported in Canada [52], China [30,53], Ireland [54,55], Spain [56] and the United States [32,33,37,57,58], at generally similar concentrations, with one measurement near manufacturing activities at concentrations exceeding 290,000 ng/L (290 mg/kg) [53]. Carpet waste and clothing were determined [33] to be sources of biotransformation precursors of PFAS compounds in the aqueous phases of anaerobic landfill model reactors.…”
Section: Pfas Landfill Leachatessupporting
confidence: 76%
“…Similar findings have been reported in Canada [52], China [30,53], Ireland [54,55], Spain [56] and the United States [32,33,37,57,58], at generally similar concentrations, with one measurement near manufacturing activities at concentrations exceeding 290,000 ng/L (290 mg/kg) [53]. Carpet waste and clothing were determined [33] to be sources of biotransformation precursors of PFAS compounds in the aqueous phases of anaerobic landfill model reactors.…”
Section: Pfas Landfill Leachatessupporting
confidence: 76%
“…This is particularly concerning, given the increased use of biosolids in recent years and the constant recirculation of PFAS between WWTPs and landfills [119]. WWTPs receive PFAS-laden leachates, and WWTP biosolids are often deposited back in landfills, creating a cycle [77,82,83]. Thus, through point source discharges of effluents, leakage or unintended releases from surface impoundments and structures, air emissions, biosolid disposal and management, and precursor reactions during treatment, WWTPs can become major contributors to the environmental release of PFAS.…”
Section: Wastewater Treatment Plantsmentioning
confidence: 99%
“…The waste containing PFAS spreads in landfill leachates. A total of 17 studies have reported the concentrations of PFAS in landfill leachates, including seven conducted in North America [27,29,45,51,[65][66][67], seven in Europe [1,64,[68][69][70][71][72], two in China [3,73], and one in Australia [74]. The concentrations of PFAS in the leachates from active landfills vary by several orders of magnitude.…”
Section: Pfas In Landfill Leachatementioning
confidence: 99%
“…Thus, landfill leachates can be a significant source of PFAS contamination in the environment. PFAS should, thus, be removed from leachates before discharging to recipients, such as WWTPs, rivers, or lakes [65].…”
Section: Pfas In Landfill Leachatementioning
confidence: 99%
See 1 more Smart Citation